New species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) of the families Philosciidae and Scleropactidae from Brazilian caves - Campos-Filho, Ivanklin Soares; Fernandes, Camile Sorbo; Cardoso, Giovanna Monticelli; Bichuette, Maria Elina; Aguiar, José Otávio; Taiti, Stefano (European Journal of Taxonomy, 2020)
After the examination of a large collection of Oniscidea from caves in the Brazilian states of Bahia, Minas Gerais, Pará, Sergipe and São Paulo, 12 species were recognized in the families Philosciidae and Scleropactidae. Four new species are described: Alboscia jotajota sp. nov. from the Açungui group; Androdeloscia akuanduba sp. nov. and Amazoniscus spica sp. nov. from the Carajás Formation; and Metaprosekia igatuensis sp. nov. from the Quadrilátero Ferrífero karst region. In addition, Atlantoscia inflata, Benthana longicornis, B. olfersii, B. picta and Paratlantoscia rubromarginata (Philosciidae) are recorded from Brazilian caves for the first time; and Benthana iporangensis, B. taeniata and Circoniscus bezzii (Scleropactidae) have the knowledge of their distribution extended to cave habitats.